If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10X + 6 = 0 Reorder the terms: 6 + -10X = 0 Solving 6 + -10X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -10X = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -10X = 0 + -6 -10X = 0 + -6 Combine like terms: 0 + -6 = -6 -10X = -6 Divide each side by '-10'. X = 0.6 Simplifying X = 0.6
| -3s=12 | | 3x=12-6 | | 16=b+2 | | -32x+16y=16 | | -2(t-5)+6t=8t-8 | | 2(3x-1)(x+5)= | | d--3=5 | | x=100y+-400 | | 5[3+2(4)]-45= | | 11(4x+12)= | | -32+16y=16 | | q-10=7 | | 11(6x+11)= | | x=1000+-100y | | 2x+40=8x+4 | | x=1000-100y | | 17+3=11g+39 | | 8(2m+4)+3(m-2)+16= | | 4x=6x-45 | | 50=2(w-5)+2w | | -4(3p+9)= | | 14x^2-42x= | | -14y=12x-28 | | 6(2x+5)+5(2x+7)= | | 19m+42= | | 100x-x=14 | | 7f+5=5f+17 | | 41x=14 | | I=(89)(.075)(.5) | | 4x-6x+2x-8x= | | 3x+(2x+10)=5 | | 18s=10 |